Calculation model of CO2 emissions for Japanese Passenger Cars. - Kakudate, Keiji (The International Journal of Life Cycle Assessment)
The quantitative macroscopic model for the CO2 emission by Japanese passenger cars is proposed in which the CO2 emission in production, use and end of life stage is analyzed in a different manner from the internationally standardized LCA according to ISO 14040s. Passenger cars are classified into regular cars, compact cars and mini cars based on their air volume displacement. These cars are scrapped from society according to their scrapping rate distribution. The effect of the change in the usage pattern of passenger cars on the amount of CO2 emission is examined and it turns out that it is not effective enough. Moreover, how much improvement of fuel economy is necessary in order to achieve the goal of the CO2 emission reduction by COP3 is also estimated. Consequently, it turns out that it must be improved by 2.42 times of the fuel economy in 1995 by the year 2010.